3.3h-3=15-12h

Simple and best practice solution for 3.3h-3=15-12h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.3h-3=15-12h equation:



3.3h-3=15-12h
We move all terms to the left:
3.3h-3-(15-12h)=0
We add all the numbers together, and all the variables
3.3h-(-12h+15)-3=0
We get rid of parentheses
3.3h+12h-15-3=0
We add all the numbers together, and all the variables
15.3h-18=0
We move all terms containing h to the left, all other terms to the right
15.3h=18
h=18/15.3
h=1+2.7/15.3

See similar equations:

| x2+8x+22=−6 | | 2x-2=4x+22 | | 3x-2(39/5)=4 | | 12x+10=24x+26 | | 6.908-g=0.173. | | -1/5x=-30 | | y/|3y+3|=-9 | | 3(x+20)-2(-x+5)=15 | | -2.6=1.9+w | | -4(4x+10)=-12x-88 | | -29=5(k+4)=60 | | (6x+8)=(3x+6) | | 1/2y=10.2 | | 9x-9=7x+132)5x+35+7x13=180 | | -4(2x+8)=3x-153 | | n-16=-15 | | 0=3x^2-18x-5 | | 4(y+12)+y=9 | | 31​ (x+6)=2x−3 | | 4(y+12)=y=9 | | 6/a=30/45 | | (5x+30)+5x=180° | | -3(2x-1)+5=8x-2 | | 8x+35=x-49 | | −8x−22=−6 | | 3x-2(2x+1)=40 | | (u-3)*10=80 | | 4x+(x+1,5)=34 | | x2−8x−12=21 | | 6y=2/5(5y-10) | | 6(5-z/5=-z | | (6x+7)=(3x-6) |

Equations solver categories